The Triple Helix in the context of global change: dynamics and challenges. (1st December 2014) - Smith, Helen Lawton; Leydesdorff, Loet
Abstract : Understanding how economies change through interactions with science and government as different spheres of activity requires both new conceptual tools and methodologies. In this paper, the evolution of the metaphor of a Triple Helix of university-industry-government relations is elaborated into an evolutionary model, and positioned within the context of global economic changes. We highlight how Triple Helix relations are both continuing and mutating, and the conditions under which a Triple Helix might be seen to be unraveling in the face of pressures on each of the three helices – university, industry, and government. The reciprocal dynamics of innovation both in the Triple Helix thesis and in the global economy are empirically explored: we find that footlooseness of high technology manufacturing and knowledge-intensive services counteract the embeddedness prevailing in medium technology manufacturing. The geographical level at which synergy in Triple Helix relations can be expected and sustained varies among nations and regions.